2008
DOI: 10.1002/jcop.20271
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrist availability, social disintegration, and suicide deaths in U.S. counties, 1990–1995

Abstract: Previous studies have found that primary care resources are associated with various health outcomes. The primary purpose of the study was to test for associations between psychiatrist availability, social disintegration and suicide rates. Data utilized were from the 2002 Area Resource File on U.S. counties (N 5 3080). Suicide rates were averaged over 6 years covering 1990 through 1995. Poisson and Negative binomial regression models were used to assess the association of psychiatrist availability and suicide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Studies in the United States consistently show that there are substantial disparities in rates and risks of suicide by race/ethnicity [ 11 , 30 , 38 , 40 ]. Racial differences in suicide have also been reported in South Africa, with whites experiencing much higher rates than Blacks, Coloureds or Asians in major South African cities [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the United States consistently show that there are substantial disparities in rates and risks of suicide by race/ethnicity [ 11 , 30 , 38 , 40 ]. Racial differences in suicide have also been reported in South Africa, with whites experiencing much higher rates than Blacks, Coloureds or Asians in major South African cities [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Divorce was measured as divorces per 1,000 resident population in 2000. The variable has been generally used as an indicator of social integration or social fragmentation [ 8 , 12 , 20 , 25 , 36 , 38 ]. Both percent college educated, 2000 and the Gini Index of income inequality, 2000 were used as socioeconomic controls.…”
Section: Methodsmentioning
confidence: 99%
“…Divisional divorce rates have no significant influence on overall suicide rates in states, but they do appear to increase mortality in three of four firearm suicide models, achieving significance at the 5% level only in one, the ownership model. Many prior studies have found a more robust, consistent association, both at the individual (Kposowa, 2000(Kposowa, , 2003 and aggregate (Breault, 1986;Kposowa, 2009) levels. Perhaps our finding is due to period or historical events: our divorce data were collected during the 2008-2009 recession.…”
Section: Discussionmentioning
confidence: 88%
“…The high quality social relationships typical of traditional forms of family life, for example, are associated in significant ways with positive mental health, as well as with decreases in morbidity and early mortality. 2 Strong familial relations also increase social integration, social regulation and support, even reduce the risk of suicide (Kposowa 2009; see also Kunce and Anderson 2002;Neumayer 2003;Breault 1986). In part also, within the family, persons discover themselves as already sustained by and within a web of pre-existing responsibilities and moral obligations (see, e.g., Lee 2014a, b;Deng 2014;.…”
Section: The Family and Human Flourishingmentioning
confidence: 99%